Rain Barrel Water Quality in Florida - Kimberly Moore; Mica McMillan; Lorna Bravo (EDIS)
Rain barrels are a great way to conserve water, save money, and contribute to a sustainable landscape. However, adoption of rain barrels is low with homeowners concerned about water quality especially from different roof types. Our analysis of nutrients showed that there was no difference in nutrient levels based on roof type. All water samples had low levels of nutrients and no detectable pathogens. Based on our analysis, the water collected from these rain barrels would be safe to use for non-potable uses in the landscape and garden.